1995
DOI: 10.1002/1097-0142(19950715)76:2<210::aid-cncr2820760208>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cryosurgery in treating colorectal metastases

Abstract: Background. The purpose of this study was to determine the effectiveness of cryosurgery as an adjunct to resection in treating patients with hepatic metastases from colorectal adenocarcinoma. Methods. Forty‐seven patients with documented metastases limited to the liver from colorectal adenocarcinoma were treated with cryosurgery with or without resection from Novermber 1987 to February 1992 and were followed until February 1994. Intraoperative ultrasound was used to map the lesions and place the cryoprobes. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(67 citation statements)
references
References 18 publications
2
64
0
1
Order By: Relevance
“…Several studies have reported the results of hepatic cryosurgery for treatment of hepatic colorectal metastases [13][14][15][16] . Sur vival after cryosurgery is probably inferior to that achieved by liver resection, but it should be noted that most of the patients undergoing cryosurgery have non-resectable tumors or later stages of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have reported the results of hepatic cryosurgery for treatment of hepatic colorectal metastases [13][14][15][16] . Sur vival after cryosurgery is probably inferior to that achieved by liver resection, but it should be noted that most of the patients undergoing cryosurgery have non-resectable tumors or later stages of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…The result is consistent with that reported by Weaver et al [15,16] who showed that patients with CEA > 100 ng/dL prior to cryosurgery had only 10 mo median survival, while the median survival of patients with CEA lower than that level was 17-19 mo. The poor outcome of patients with higher CEA may be related to the biological behavior of CEA-secreting tumors.…”
Section: Factors Influencing Survival Of Patientmentioning
confidence: 99%
“…It was as effective as surgical resection for treating metastases to the liver from colorectal carcinomas. 8,9 Because it is a focal treatment, it has the advantage over surgical resection of destroying only the necessary amount of liver tissue, while sparing the uninvolved liver tissue. This is of particular importance for patients with more than four liver metastases because most of them cannot undergo curative liver resection.…”
mentioning
confidence: 99%
“…The curative potential with cryotherapy in CLMs had been further demonstrated by the 10-year survival of 13% [82]. The available literature on treatment of CLMs with hepatic cryotherapy reports median, 1-, 2-, 3-, 4-, 5-, and 10-year overall survivals of 18 -33 months [56,57,[59][60][61]63,64,66,[70][71][72][73]77,78,[80][81][82][83]85], 78% -92% [56,58,61,63,66,[70][71][72]80,82,83,86], 47% -66% [61,63,66,[70][71][72]80,83,86,87], 29% -50% [56,58,60,63,66,72,80,8...…”
Section: Survivalmentioning
confidence: 99%
“…In some centres, edge cryotherapy had been employed to suboptimal resection margins obtaining median and 5-year survivals of 39 months and 36% [69,82,88,89], respectively; resembling that of clear-margin resections [82,84,[88][89][90]. The median, 1-, 2-, 3-, 5-, and 10-year disease-free survivals reported were 9 -27 months [59,72,77,78,81,82,84,86,88], 38% -41% [58,78,82,86], 16% -35% [58,78,86], 8% -17% [78,82,86], 12% -13% [59,82], and 11% [82], respectively (Figure 4). Approximately 80% of surgically treated CLMs will develop some form of recurrence; and the pattern of recurrence had been variably described [61,64,70,71,78,80,82,86].…”
Section: Recurrencementioning
confidence: 99%